Gaya Bahasa Perulangan Pada Lirik Lagu Nadin Amizah Dalam Album Selamat Ulang Tahun : Kajian Stilistika - Tasya Fadillah; Haris Sutan Lubis; Emma Marsella (Departement of Mathematics Education, 2024)
This research aims to discuss the language style of repetition and messages in the lyrics of Nadin Amizah's song in the Happy Birthday Album. The theory applied in this research is stylistic theory. Language style plays an important role in assessing the beauty of a literary work. Tarigan states that there are four types of language styles, namely, comparative language styles, conflicting language styles, linking language styles, and repetition language styles. This research aims to describe the repetitive language style and messages contained in the Happy Birthday album by Nadin Amizah. The research method used is a qualitative descriptive method with data collection techniques using note-taking techniques. The data in this research are the song lyrics in the Happy Birthday album. From the research results, six types of repetition language styles were found, namely: (1) alliteration, (2) assonance, (3) anaphora, (4) mesodilopsis, (5) epizeukis, and (6) epanalepsis. Furthermore, in this album there are messages about the relationship between the author and the people around him, such as family, friends and partners, which are explained by feelings of hurt and trauma.